2nd International Congress on Acoustical and Vibratory Surveillance Methods and Diagnostic Techniques - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1995)
The Congress is hosted by a research centre (D.E.R.) of Electricité de France (E.D.F.)